1990
DOI: 10.1111/j.1445-5994.1990.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial iron overload with possible autosomal dominant inheritance

Abstract: A 96 member Melanesian kindred with 31 cases of iron overload is reported. Liver biopsies from 19 of these patients showed features similar to those of genetic haemochromatosis in Caucasians, but in contrast to the previous reported HLA-linked autosomal recessive pattern of inheritance for haemochromatosis, this family shows a pattern that is most consistent with autosomal dominant inheritance. This is suggested by involvement of three and possibly four consecutive generations, with a high frequency of transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 1 publication
0
31
0
2
Order By: Relevance
“…3 Iron overload can occur in nonwhites and may be related to as-yet-undiscovered genetic mutations, environmental factors, or both. [4][5][6][7][8][9] The Hemochromatosis and Iron Overload Screening (HEIRS) study was designed to evaluate the prevalence, genetic and environmental determinants, and potential clinical, personal, and societal effects of iron overload and hemochromatosis in a multicenter, multiethnic sample of 101,168 primary care adults 25 years of age or older. This article reports findings from the first, or screening, stage of the study.…”
Section: Resultsmentioning
confidence: 99%
“…3 Iron overload can occur in nonwhites and may be related to as-yet-undiscovered genetic mutations, environmental factors, or both. [4][5][6][7][8][9] The Hemochromatosis and Iron Overload Screening (HEIRS) study was designed to evaluate the prevalence, genetic and environmental determinants, and potential clinical, personal, and societal effects of iron overload and hemochromatosis in a multicenter, multiethnic sample of 101,168 primary care adults 25 years of age or older. This article reports findings from the first, or screening, stage of the study.…”
Section: Resultsmentioning
confidence: 99%
“…72 Subsequently it was shown that the dominant disorder is usually characterized by iron accumulation in macrophages but normal/low transferrin saturation. These atypical features indicate a different pathogenesis than in other forms of hemochromatosis.…”
Section: Ferroportin Disease: a Hemochromatosis-related Dual Face Dismentioning
confidence: 99%
“…6,7 Hemochromatosis families with apparent autosomal dominant inheritance have been reported. [8][9][10] Recently, a new locus for an autosomal dominant form of hemochromatosis (HFE4) was identified on chromosome 2q32. Two missense mutations in the ferroportin1 gene, which maps to this region, were detected in 2 families with autosomal dominant hemochromatosis from the Netherlands and Italy.…”
Section: Introductionmentioning
confidence: 99%